Anion-cation doped manganese dioxide prepared based on fluidized bed technology and application of anion-cation doped manganese dioxide in zinc ion battery
The preparation of anion- and cation-doped manganese dioxide using fluidized bed technology has solved the problems of low electronic conductivity, slow diffusion kinetics, and high preparation cost of manganese dioxide, enabling efficient mass production and improving the electrochemical performance of zinc-ion batteries.
Patent Information
- Application Number
- CN202511560826.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-29
- Publication Date
- 2026-01-23
AI Technical Summary
In existing technologies, manganese dioxide has low electronic conductivity, slow diffusion kinetics, poor structural stability, high preparation cost, and is difficult to mass-produce.
Anion- and cation-doped manganese dioxide was prepared using fluidized bed technology. A cation-doped manganese carbonate precursor was generated by co-precipitation. The gas-solid reaction was carried out in a fluidized bed under an inert argon gas carrier, combined with the reduction reaction of NH3 or H2S gas, to achieve synergistic doping of anions and cations.
This method improves the diffusion kinetics and structural stability of manganese dioxide, reduces preparation costs, enables mass production, and has promising prospects for industrial applications.
Smart Images

Figure CN121377121A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage technology, specifically to a method for preparing anion and cation-doped manganese dioxide based on fluidized bed technology and its application in zinc-ion batteries. Background Technology
[0002] Rechargeable lithium-ion batteries provide power for portable electronic products, electric vehicles, and more. However, the scarcity of lithium resources and the availability of flammable organic electrolytes constrain lithium-ion batteries due to cost and safety issues. Aqueous batteries, with their low cost and intrinsic safety, have become a research hotspot for next-generation energy storage media. Among them, zinc-ion batteries have attracted much attention due to their abundant zinc resources, good chemical stability, and neutral electrolyte. However, the cathode materials suitable for aqueous zinc-ion batteries limit their rapid development. Among various feasible cathode materials, manganese dioxide has become a research hotspot due to its high operating voltage, low cost, and considerable capacity. Of course, manganese dioxide cathode materials also have shortcomings such as low electronic conductivity, slow diffusion kinetics, and poor structural stability. Heteroionic doping, as an important strategy for modifying manganese dioxide, has been proven to be an effective way to improve these shortcomings.For example, copper ion doping improves the electronic conductivity of manganese dioxide materials (Manipulating intercalation-extraction mechanisms in structurally modulated δ-MnO2 nanowires for high-performance aqueous zinc-ion batteries [J]. Chemical Engineering Journal, 2022, 433P3, 433P3); molybdenum ion doping improves the diffusion kinetics of manganese dioxide materials (Mo-pre-intercalated MnO2 cathode with highly stable layered structure and expanded interlayer spacing for aqueous Zn-ion batteries [J]. ACS Applied Materials & Interfaces, 2023, 15, 856); bismuth ion doping improves the structural stability of manganese dioxide materials (Molecular tailoring of MnO2 by bismuth doping to achieve aqueous zinc-ion battery with capacitor-level durability [J]. Energy Storage Materials, 2022, 48, 212); and sulfur ion doping reduces the charge resistance of zinc ions in the bulk phase of manganese dioxide, thereby improving its diffusion kinetics (Uncovering sulfur The doping effect in MnO2 nanosheets as an efficient cathode for aqueous zinc ion battery[J]. Energy Storage Materials, 2022, 47, 424-433., and the doping of nitrogen ions improves the electronic conductivity of manganese dioxide (Non-metal anion doping construction of the durable cathode with optimized oxygenvacancies in aqueous zinc-ion batteries[J]. Nano Research Energy, 2025.).However, current hetero-ion-doped manganese dioxide research mostly focuses on doping with single anions or cations, making it difficult to achieve a strategy of synergistic doping of anions and cations, which can yield greater improvement results. Furthermore, current methods for preparing hetero-ion-doped manganese dioxide all employ hydrothermal methods, which require sophisticated equipment, have low yields, and are costly, failing to meet the requirements for large-scale production. Therefore, new production technologies are urgently needed to achieve efficient mass production.
[0003] In view of this, this application proposes a method for preparing anion- and cation-doped manganese dioxide based on fluidized bed technology. This method not only realizes the anion- and cation-co-doping strategy, but also has high yield, short process, and simple process, which greatly reduces the preparation cost of anion- and cation-doped manganese dioxide and breaks through the technical bottleneck of anion- and cation-doped manganese dioxide preparation. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing anion and cation-doped manganese dioxide based on fluidized bed technology and its application in zinc-ion batteries, thereby solving the problems of low conductivity, slow diffusion kinetics, poor structural stability, high preparation cost, and difficulty in large-scale preparation of manganese dioxide in the prior art.
[0005] To address the above technical problems, the technical solution of the present invention will be described in detail.
[0006] This invention provides a method for preparing anion- and cation-doped manganese dioxide materials based on fluidized bed technology, comprising the following steps:
[0007] (1) Soluble heterogeneous cations (A) + The salt is dissolved in an aqueous solution containing divalent manganese salt. Sodium carbonate solution is added to the solution while stirring until a cation-doped manganese carbonate precipitate (A-MnCO3) is formed.
[0008] (2) Place the A-MnCO3 obtained in step (1) into a fluidized bed, turn on the gas circulation pump of the fluidized bed under an argon atmosphere to keep the A-MnCO3 particles in a suspended state. The temperature inside the fluidized bed is 300~450℃ and the fluidization time is 2~15 h. During this stage, A-MnCO3 decomposes to produce cation-doped manganese dioxide (A-MnO2) and CO2 gas. CO2 is adsorbed and eliminated by the filter device.
[0009] (3) After A-MnCO3 is completely decomposed into A-MnO2, NH3 or H2S gas is introduced into the fluidized bed cavity through the gas supply port. Argon gas carries NH3 or H2S through the fluidized bed and fully contacts the A-MnO2 particles, causing a reduction reaction to obtain anionic nitrogen or sulfur doped and cation (A +Manganese dioxide doped with (A / N-MnO2 or A / S-MnO2).
[0010] Preferably, in step (1), the soluble heterogeneous cation salt is any one or a mixture of metal cation sulfates, nitrates, chlorides, phosphorus, phosphates, acetates, and some soluble metal cation organic salts, such as aluminum sulfate, aluminum nitrate, aluminum chloride, sodium aluminate, copper sulfate, copper nitrate, copper chloride, copper acetate, bismuth sulfate, bismuth nitrate, calcium sulfate, calcium nitrate, calcium chloride, calcium acetate, cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt acetate, nickel sulfate, nickel nitrate, nickel chloride, nickel acetate, magnesium sulfate, magnesium nitrate, magnesium chloride, magnesium acetate, sodium tungstate, tungsten chloride, zinc sulfate, zinc nitrate, zinc chloride, zinc acetate, lanthanum nitrate, yttrium nitrate, indium nitrate, silver nitrate, cerium nitrate, sodium chloride, sodium nitrate, sodium oxide, potassium chloride, potassium nitrate, potassium oxide, and their hydrated compounds; the divalent manganese salt is any one or a mixture of manganese sulfate, manganese nitrate, manganese chloride, manganese bromide, manganese acetate, and their hydrated compounds.
[0011] Preferably, in step (1), the concentration ratio of divalent manganese salt solution to sodium carbonate solution is 1:1 to 1:5, and the concentration ratio of soluble heterocation to divalent manganese salt is 1:1 to 1:200. Sodium carbonate is an important compound that promotes the formation of precipitates between divalent manganese and soluble heterocations. When too much sodium carbonate is added, a large amount of carbonate remains in the solution after the divalent manganese and soluble heterocations have formed a precipitate, resulting in a waste of carbonate. When too little sodium carbonate is added, the divalent manganese and soluble heterocations do not precipitate completely, resulting in a waste of divalent manganese and soluble heterocations. In addition, it can also cause a deviation in the content of heterocations in manganese carbonate and manganese dioxide.
[0012] Preferably, in step (2), the temperature inside the fluidized bed is 300~450℃, preferably 400℃. If the temperature inside the fluidized bed is too low, it is not conducive to the decomposition of A-MnCO3 particles. If the temperature inside the fluidized bed is too high (greater than 500℃), the A-MnCO3 particles will first undergo a decomposition reaction, generating A-MnO2 and CO2 gas. Subsequently, A-MnO2 will undergo another decomposition reaction, generating A-Mn2O3 or A-Mn3O4. The fluidization time is 2~15 h, preferably 4 h. The heating and cooling rates inside the fluidized bed are both 5~10℃ / min.
[0013] Preferably, in step (3), NH3 or H2S gas is introduced into the fluidized bed cavity through the gas supply port, and the NH3 or H2S gas accounts for 0.5% to 20% of the carrier argon gas integral. The volume fraction of NH3 or H2S in argon is closely related to the degree of reduction and structural stability of A-MnO2. When the volume fraction of NH3 or H2S in argon is too high, A-MnO2 is over-reduced, and the prepared A / N-MnO2 or A / S-MnO2 contains a large amount of trivalent manganese. Due to the difference in bond length between trivalent and tetravalent manganese, the prepared A / N-MnO2 or A / S-MnO2 has poor structural stability and is prone to the Jan Taylor effect, losing its tunnel or layered structure. When the volume fraction of NH3 or H2S in argon is too low, A-MnO2 is insufficiently reduced, and the prepared A / N-MnO2 or A / S-MnO2 has a low doping amount of N or S, resulting in poor anion modification effect.
[0014] Preferably, in step (3), argon gas carries NH3 or H2S through a fluidized bed and fully contacts the A-MnO2 particles to undergo a reduction reaction. The temperature at which the reduction reaction occurs is 300~500℃, preferably 350℃. The reaction time is 1~15 h, preferably 2 h.
[0015] The technical features of this invention are as follows:
[0016] (1) One of the main technical features of this invention is the preparation of anion- and cation-doped manganese dioxide using a fluidized bed apparatus based on gas-solid reaction. This invention first uses a co-precipitation method to prepare cation- and cation-doped manganese dioxide. + A manganese carbonate precursor (A-MnCO3) doped with cations is introduced into a fluidized bed reactor. Argon gas is used as the carrier gas to suspend the A-MnCO3 particles. The temperature within the fluidized bed is set to 300–450°C. At this temperature, the A-MnCO3 particles decompose, producing cation-doped manganese dioxide particles (A-MnO2) and CO2 gas. The CO2 gas is removed by a circulating filtration system. Once the A-MnCO3 particles are completely decomposed into A-MnO2, the temperature within the fluidized bed is set to 300–500°C. At this temperature, NH3 or H2S gas is introduced into the fluidized bed through a gas inlet. The volume fraction of NH3 or H2S is detected and controlled within the range of 0.5%–20% using a gas concentration probe. Argon gas carrying NH3 or H2S gas passes through a fluidized bed and fully contacts suspended A-MnO2 particles, causing a reduction reaction to produce anionic nitrogen or sulfur doped and cation (A + Manganese dioxide doped with (A / N-MnO2 or A / S-MnO2).
[0017] (2) One of the main technical features of this invention is the use of NH3 or H2S, which have reducing properties and contain anions, as an anion doping gas source to prepare anion- and cation-doped manganese dioxide. Nitrogen and sulfur atoms have similar atomic configurations to oxygen atoms, but their electronegativity is significantly lower than that of oxygen atoms. Therefore, substitutional doping with nitrogen or sulfur atoms to oxygen atoms in manganese dioxide can significantly reduce the electrostatic resistance within the manganese dioxide lattice and improve the diffusion kinetics of manganese dioxide. In addition, replacing oxygen atoms in manganese dioxide with nitrogen and sulfur atoms can also change the charge distribution in the manganese dioxide crystal, thereby improving the intrinsic conductivity of manganese dioxide.
[0018] (3) Doped cations (A) + The heterovalent cations enter the precursor manganese carbonate (A-MnCO3) in the form of co-precipitate. During thermal decomposition, the doped heterocations diffuse into the tunnels of manganese dioxide, forming stable ionic bonds with oxygen atoms above and below the tunnels, acting as interlayer pillars to stabilize the layered structure of manganese dioxide. Some cations with larger ionic radii can also increase the interlayer spacing, improving the diffusion kinetics of charge carriers between manganese dioxide layers. In addition, some cations with ionic radii similar to those of tetravalent manganese ions can substitute for tetravalent manganese in manganese dioxide, providing electrochemical reactivity and increasing the electrochemical capacity of manganese dioxide.
[0019] This invention also provides anion and cation doped manganese dioxide prepared by the method, and the application of the material as a positive electrode material in zinc-ion batteries. The zinc-ion battery is an aqueous zinc-ion symmetric battery, an aqueous zinc-ion half-cell, an aqueous zinc-ion primary full cell, or an aqueous zinc-ion secondary full cell, using zinc foil or zinc powder as the negative electrode and a liquid or gel rich in zinc-ion soluble salts as the electrolyte.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) Compared with undoped and single cation or anion doped manganese dioxide, anion and cation doped manganese dioxide has higher diffusion kinetics, conductivity and structural stability, and has excellent electrochemical performance as a cathode material for zinc-ion batteries.
[0022] (2) Compared with the traditional hydrothermal method for preparing heterogeneous ion-doped manganese dioxide, the present invention places the high-cost cation-doped salt in the precursor manganese carbonate precipitate, which improves the utilization rate of heterogeneous doped cations and reduces costs.
[0023] (3) The fluidized bed technology used in this invention puts the entire production of manganese dioxide in a closed and circulating process. On the one hand, it absorbs carbon dioxide in the production process, reduces carbon emissions, and protects the environment; on the other hand, the closed and circulating process improves the utilization rate of NH3 or H2S gas sources.
[0024] (4) This invention utilizes gas-solid reaction based on fluidized bed technology to achieve substitution doping of nitrogen or sulfur elements. In addition, the gas-solid reaction temperature and reaction time can be flexibly controlled to achieve gradient doping or uniform doping distribution of nitrogen or sulfur elements in manganese dioxide, thus realizing controllable adjustment of nitrogen or sulfur.
[0025] (5) Compared with the traditional hydrothermal method for preparing heterogeneous ion-doped manganese dioxide, the method for preparing anion- and cation-doped manganese dioxide based on fluidized bed technology is simple to operate and has a short process flow; it has low equipment requirements and low equipment investment; it has high output and low energy consumption, and can realize batch and continuous production, and has good industrial application prospects.
[0026] In summary, this invention prepares anion- and cation-doped manganese dioxide based on fluidized bed technology. This preparation method can solve the problems of low electronic conductivity, poor kinetic performance, unstable structure, and difficulty in large-scale preparation of manganese dioxide as a cathode material for zinc-ion batteries, thus promoting the development and progress of manganese-based materials as cathodes of zinc-ion batteries. Attached Figure Description
[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.
[0028] Figure 1 This is a schematic diagram of the fluidized bed used in this invention;
[0029] Figure 2 The X-ray diffraction pattern of the Al-MnCO3 precipitate prepared in Example 1;
[0030] Figure 3 The X-ray diffraction pattern of Al / N-MnO2 prepared in Example 1;
[0031] Figure 4 This is a SEM image of the Al / N-MnO2 prepared in Example 1;
[0032] Figure 5 The image shows the EDS diagram of Al / N-MnO2 prepared in Example 1.
[0033] Figure 6 The graph shows the long-cycle performance of a zinc-ion battery using the Al / N-MnO2 prepared in Example 1 as the positive electrode at a current density of 2 A / g.
[0034] Figure 7 The XRD pattern of the Bi-doped manganese oxide prepared in Comparative Example 1 is shown.
[0035] Figure 8 SEM image of the undoped MnO2 prepared in Comparative Example 1;
[0036] Figure 9 The graph shows the long-cycle performance of a zinc-ion battery using undoped MnO2 prepared in Comparative Example 1 as the positive electrode at a current density of 2 A / g. Detailed Implementation
[0037] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.
[0038] Example 1
[0039] (1) Dissolve 1.10 g of soluble heterogeneous cation salt Al2(SO4)3 in 100 mL of MnSO4 solution with a concentration of 0.5 mol / L, and add 100 mL of Na2CO3 solution with a concentration of 1 mol / L while stirring to generate aluminum ion-doped manganese carbonate precipitate (Al-MnCO3).
[0040] (2) Place the Al-MnCO3 prepared in step (1) into a fluidized bed, turn on the gas circulation pump of the fluidized bed under an argon atmosphere to keep the Al-MnCO3 particles in a suspended state. The temperature inside the fluidized bed is 400℃ and the fluidization time is 4 h. During this stage, Al-MnCO3 is completely decomposed to produce aluminum ion-doped manganese dioxide (Al-MnO2) and CO2 gas. CO2 is adsorbed and eliminated by the filter device.
[0041] (3) Adjust the temperature in the fluidized bed chamber to 350℃ and add NH3 gas into the fluidized bed chamber through the gas inlet so that the volume of NH3 in the fluidized bed chamber accounts for 5% of the volume of the inert gas argon. The argon carries NH3 through the fluidized bed and fully contacts the Al-MnO2 particles to undergo a reduction reaction. The fluidization reaction time is 2 h to obtain aluminum ion and nitrogen atom doped manganese dioxide (Al / N-MnO2).
[0042] Figure 1 This is a schematic diagram of the fluidized bed used in Examples 1 and 2.
[0043] Figure 2 The image shows the X-ray diffraction pattern of the Al-MnCO3 precursor prepared in Example 1. It exhibits good crystallinity, matches well with PDF card JCPDS NO. 86-0172, and shows no alumina-related impurity peaks, indicating that aluminum ions have entered the MnCO3 bulk phase.
[0044] Figure 3The image shows the XRD pattern of Al / N-MnO2 prepared in Example 1. It exhibits good crystallinity, matches well with PDF card JCPDS NO.44-0141, and has no alumina-related impurity phases, indicating that aluminum ions and nitrogen atoms have entered the bulk MnO2 phase, and that MnO2 maintains a good tunnel structure.
[0045] Figure 4 The image shows a SEM image of the Al / N-MnO2 prepared in Example 1. The Al / N-MnO2 exhibits a spherical morphology with a diameter of 1-2 micrometers. Due to the doping of aluminum ions and the nitriding process in the fluidized bed, its spherical surface exhibits a loose and porous morphology, which is beneficial for the wetting of the liquid electrolyte.
[0046] Figure 5 The image shows the EDS diagram of Al / N-MnO2 prepared in Example 1. It can be seen that Mn, O, Al, and N elements are uniformly distributed within the spherical profile, demonstrating the successful doping of Al and N elements into the manganese dioxide bulk phase using fluidized bed technology. The successful incorporation of aluminum cations and nitrogen anions will improve the overall electrochemical performance of manganese dioxide.
[0047] Figure 6 This is a graph showing the long-cycle performance of Al / N-MnO2 as the positive electrode of a zinc-ion battery in Example 1 at a current density of 2 A / g. The horizontal axis represents the number of cycles, and the vertical axis represents the discharge specific capacity in mAh / g. It can be seen that the initial discharge specific capacity is 110.1 mAh / g, which increases to 180.6 mAh / g after 60 cycles of electrochemical activation. After 1150 cycles, the capacity reaches its maximum of 305.2 mAh / g, and after 3200 cycles, it still retains a residual specific capacity of 222.9 mAh / g, with a coulombic efficiency of 99.8%. Thanks to the synergistic doping of aluminum ions and nitrogen atoms, Al / N-MnO2 achieves excellent electrochemical performance.
[0048] Example 2
[0049] (1) Dissolve 1.2 g of soluble heterogeneous cation salt Ni(NO3)2 in 100 mL of MnSO4 solution with a concentration of 0.5 mol / L, and add 100 mL of Na2CO3 solution with a concentration of 0.8 mol / L to the solution while stirring to generate nickel ion doped manganese carbonate precipitate (Ni-MnCO3).
[0050] (2) Place the Ni-MnCO3 prepared in step (1) into a fluidized bed, turn on the gas circulation pump of the fluidized bed under an argon atmosphere to keep the Ni-MnCO3 particles in a suspended state, the temperature inside the fluidized bed is 380℃, and the fluidization time is 5 h. During this stage, Ni-MnCO3 is completely decomposed to produce nickel ion-doped manganese dioxide (Ni-MnO2) and CO2 gas. CO2 is adsorbed and eliminated by the filter device.
[0051] (3) Adjust the temperature inside the fluidized bed chamber to 350℃, and introduce H2S gas into the fluidized bed chamber through the gas inlet so that the volume of H2S in the fluidized bed chamber accounts for 3% of the volume of the inert gas argon. The argon carries H2S through the fluidized bed and fully contacts the Ni-MnO2 particles to undergo a reduction reaction. The fluidization reaction time is 2 h to obtain nickel ion and sulfur atom doped manganese dioxide (Ni / S-MnO2).
[0052] Comparative Example 1
[0053] (1) Dissolve 2.43 g of soluble heterogeneous cation salt Bi(NO3)3 in 100 mL of MnSO4 solution with a concentration of 0.5 mol / L, and add 100 mL of Na2CO3 solution with a concentration of 0.8 mol / L to the solution while stirring to generate bismuth ion-doped manganese carbonate precipitate (Bi-MnCO3).
[0054] (2) Place the Bi-MnCO3 prepared in step (1) into a fluidized bed, turn on the gas circulation pump of the fluidized bed under an argon atmosphere to keep the Bi-MnCO3 particles in a suspended state, the temperature inside the fluidized bed is 550℃, and the fluidization time is 3 h. During this stage, Bi-MnCO3 undergoes a decomposition reaction to produce bismuth ion-doped manganese oxides and CO2 gas, while CO2 is adsorbed and eliminated by the filter device.
[0055] (3) Adjust the temperature inside the fluidized bed to 350℃ and add NH3 gas into the fluidized bed through the gas inlet so that the volume of NH3 in the fluidized bed is 5% of the volume of the inert gas argon. The argon carries NH3 through the fluidized bed and fully contacts the Al-MnO2 particles to undergo a reduction reaction. The fluidization reaction time is 2 h to obtain bismuth ion and nitrogen atom doped manganese oxide compound.
[0056] Figure 7The image shows the X-ray diffraction pattern of the bismuth ion and nitrogen atom-doped manganese oxide compound prepared in Comparative Example 1. Because the temperature inside the fluidized bed chamber in step 2 was 550℃, this fluidization temperature was too high. Bi-MnCO3 first underwent a decomposition reaction to generate Bi-MnO2. Subsequently, the excessively high temperature caused Bi-MnO2 to undergo another phase transition, generating Bi-Mn3O4 (Mn3O4 corresponds to PDF card JCPDS NO. 24-0734). During the subsequent nitriding process, its crystal phase could not be changed, thus generating Bi / N-Mn3O4.
[0057] Comparative Example 2
[0058] (1) Step (1): Take 100 mL of 0.5 mol / L MnSO4 solution and add 100 mL of 0.8 mol / L Na2CO3 solution to the solution while stirring to generate manganese carbonate precipitate (MnCO3).
[0059] (2) Place the MnCO3 prepared in step (1) into a crucible, and place the crucible containing the MnCO3 precipitate into a tube furnace under an argon protective atmosphere, and heat it to 400℃ at 5℃ / min and keep it at that temperature for 4 h.
[0060] (3) Cool the tube furnace to room temperature and collect the black powder, which is the undoped MnO2.
[0061] Figure 8 The image shows an SEM image of undoped MnO2 prepared using non-fluidized bed technology in Comparative Example 2. The undoped MnO2 exhibits a spherical morphology with a diameter of 1-2 micrometers. Since there is no cation doping to alter its nucleation process or the nitriding or sulfidation reduction process in the fluidized bed, the surface of the undoped MnO2 is dense and compact, which is not conducive to carrier diffusion and electrolyte wetting.
[0062] Figure 9 The graph shows the long-cycle performance of undoped MnO2, prepared using non-fluidized bed technology, as the positive electrode of a zinc-ion battery in Example 2, at a current density of 2 A / g. The horizontal axis represents the number of cycles, and the vertical axis represents the discharge specific capacity in mAh / g. It can be seen that the initial discharge specific capacity is 164.5 mAh / g, reaching its peak of 233.3 mAh / g in the second cycle. After 3000 cycles, the remaining capacity is only 120.0 mAh / g, indicating a severe capacity decay of the undoped MnO2.
[0063] Test case
[0064] Using aluminum / nitrogen-doped manganese dioxide (Al / N-MnO2) prepared in Example 1 and undoped MnO2 prepared in Comparative Example 1 as electrode materials, half-cells were assembled for electrochemical performance testing. 9 mg of conductive agent acetylene black, 9 mg of PVDF binder, and 1.5 mL of N-methylpyrrolidone solvent were added to 42 mg of Al / N-MnO2 or undoped MnO2, respectively, to form a homogeneous slurry. The slurry was uniformly coated onto carbon paper with a diameter of 10 mm. The coated electrode sheets were then dried in a vacuum drying oven at 80 °C for 12 h. The coin cell encapsulation process was as follows: a 0.1 mm thick zinc sheet was used as the negative electrode, the prepared electrode sheet as the positive electrode, glass fiber filter paper as the separator, and a CR2032 coin cell casing was used for encapsulation. The encapsulation environment was room temperature air, and the electrolyte was a 2 mol / L ZnSO4 + 0.2 mol / L MnSO4 aqueous solution.
[0065] The experimental results show that:
[0066] Within a voltage window of 0.9–1.85 V and a current density of 2 A / g, the Al / N-MnO2 electrode exhibited an initial discharge specific capacity of 110.1 mAh / g. After 60 cycles of electrochemical activation, it achieved a specific capacity of 180.6 mAh / g. After 1150 cycles, its capacity reached a peak of 305.2 mAh / g, and after 3200 cycles, it still retained a residual specific capacity of 222.9 mAh / g with a coulombic efficiency of 99.8%. Testing verified that the Ni / S-MnO2 prepared in Example 2 also exhibited a specific capacity of 205.3 mAh / g and a coulombic efficiency of 99.9% after 3000 cycles. However, the initial discharge specific capacity of undoped MnO2 was 164.5 mAh / g, and it reached its maximum capacity of 233.3 mAh / g in the second cycle. After 3000 cycles, its remaining capacity was only 120.0 mAh / g, indicating that the capacity of undoped MnO2 was severely degraded.
[0067] Both Al / N-MnO2 and Ni / S-MnO2 exhibit high discharge specific capacity under high current, mainly due to the fast diffusion kinetics and high electronic conductivity imparted to manganese dioxide by N and S anion doping. Their excellent long-cycle stability is closely related to the high structural stability of manganese dioxide imparted by Al and Ni cation doping. Therefore, anion- and cation-doped manganese dioxide prepared based on fluidized bed technology possesses excellent comprehensive electrochemical performance as a cathode in zinc-ion batteries.
[0068] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for preparing anion- and cation-doped manganese dioxide based on fluidized bed technology, characterized in that, Includes the following steps: (1) Soluble heterogeneous cations (A) + The salt is dissolved in an aqueous solution containing divalent manganese salt. Sodium carbonate solution is added to the solution while stirring until a cation-doped manganese carbonate precipitate (A-MnCO3) is formed. (2) Place the A-MnCO3 obtained in step (1) into a fluidized bed, turn on the gas circulation pump of the fluidized bed under an argon atmosphere to keep the A-MnCO3 particles in a suspended state. The temperature inside the fluidized bed is 300~450℃ and the fluidization time is 2~15 h. During this stage, A-MnCO3 decomposes to produce cation-doped manganese dioxide (A-MnO2) and CO2 gas. CO2 is adsorbed and eliminated by the filter device. (3) After A-MnCO3 is completely decomposed into A-MnO2, NH3 or H2S gas is introduced into the fluidized bed cavity through the gas supply port. Argon gas carries NH3 or H2S through the fluidized bed and fully contacts the A-MnO2 particles, where a reduction reaction occurs to produce anionic nitrogen or sulfur doped and cation (A + Manganese dioxide doped with (A / N-MnO2 or A / S-MnO2).
2. The method for preparing anion- and cation-doped manganese dioxide based on fluidized bed technology according to claim 1, characterized in that, In step (1), the soluble heterocation (A) + Salts are any one or a mixture of metal cation sulfates, nitrates, chlorides, phosphorus, phosphates, acetates, and some soluble metal cation organic salts, such as aluminum sulfate, aluminum nitrate, aluminum chloride, sodium aluminate, copper sulfate, copper nitrate, copper chloride, copper acetate, bismuth sulfate, bismuth nitrate, calcium sulfate, calcium nitrate, calcium chloride, calcium acetate, cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt acetate, nickel sulfate, nickel nitrate, nickel chloride, nickel acetate, magnesium sulfate, magnesium nitrate, magnesium chloride, magnesium acetate, sodium tungstate, tungsten chloride, zinc sulfate, zinc nitrate, zinc chloride, zinc acetate, lanthanum nitrate, yttrium nitrate, indium nitrate, silver nitrate, cerium nitrate, sodium chloride, sodium nitrate, sodium oxide, potassium chloride, potassium nitrate, potassium oxide, and their hydrated compounds; divalent manganese salts are any one or a mixture of manganese sulfate, manganese nitrate, manganese chloride, manganese bromide, manganese acetate, and their hydrated compounds.
3. The method for preparing anion- and cation-doped manganese dioxide based on fluidized bed technology according to claim 1, characterized in that, In step (1), the concentration ratio of divalent manganese salt solution to sodium carbonate solution is 1:1 to 1:5, and the concentration ratio of soluble heterogeneous cation to divalent manganese salt is 1:1 to 1:
200.
4. The method for preparing anion- and cation-doped manganese dioxide based on fluidized bed technology according to claim 1, characterized in that, In step (2), the temperature inside the fluidized bed is 300~450℃, preferably 400℃. The fluidization time is 2~15 h, preferably 4 h. The heating and cooling rates inside the fluidized bed are both 5~10℃ / min.
5. The method for preparing anion- and cation-doped manganese dioxide based on fluidized bed technology according to claim 1, characterized in that, In step (3), NH3 or H2S gas is introduced into the sulfurized bed cavity through the gas injection port. The NH3 or H2S gas accounts for 0.5% to 20% of the carrier argon gas.
6. The method for preparing anion- and cation-doped manganese dioxide based on fluidized bed technology according to claim 1, characterized in that, In step (3), argon gas carries NH3 or H2S through a fluidized bed and fully contacts A-MnO2 particles to undergo a reduction reaction. The temperature at which the reduction reaction occurs is 300~500℃ and the time for the reduction reaction is 1~15 h.
7. The anion- and cation-doped manganese dioxide material prepared by the method according to any one of claims 1 to 6.
8. The application of the anion and cation doped manganese dioxide as a positive electrode material in zinc-ion batteries according to claim 7.
9. The application according to claim 8, characterized in that, The zinc-ion battery is an aqueous zinc-ion symmetrical battery, an aqueous zinc-ion half-cell, an aqueous zinc-ion primary full cell, or an aqueous zinc-ion secondary full cell.